(untitled) (Journal of Academic Research, 2024)
Inhalation of secondhand smoke causes significant damage to the body, which may harm the occurrence of lung infections and poisoning of some organs of the body. This study aimed to assess histological and hematological morphological changes and the effect of smoking cigarettes on red and white blood cells in white rats inhaled for acute doses for 3, 12, and 20 hours. Rats were exposed to cigarette smoke for periods from 3 to 24 hours. Most cigarette smoke was inhaled through the respiratory tract in the courtroom containing air openings for breathing and preventing choking of rats. Chemical techniques were employed to analyze liver and kidney enzymes in blood and tissue samples to study tissue changes. The findings revealed that acute exposure to smoked cigarettes led to immobility and impaired movement in rats. The analysis results indicated notable alterations in the liver and kidney tissues, particularly in the lungs. The study demonstrated elevated levels of liver and kidney enzymes in the various rat blood groups, suggesting dysfunction in the liver and kidneys. These heightened enzyme levels were statistically significant (p < 0.05). Moreover, the study revealed the breakdown of red blood cells and reduced hemoglobin levels upon acute inhalation of cigarette smoke. The toxic effects of smoke inhalation were observed in the blood cell count, indicating the occurrence of inflammation, along with a substantial increase in platelet count, implying an increased risk of blood clot formation. Ultimately, exposure to secondhand smoke results in poisoning, suffocation, damage to vital organs, loss of functionality, and heightened contamination of living organisms. Therefore, it is crucial to avoid exposure to secondhand smoke.